Patient selection, peri-procedural management, and ablation techniques for catheter ablation of atrial fibrillation: an EHRA survey. Issue 2 (13th December 2022) - Iliodromitis, Konstantinos; Lenarczyk, Radoslaw; Scherr, Daniel; Conte, Giulio; Farkowski, Michal M; Marin, Francisco; Garcia-Seara, Javier; Simovic, Stefan; Potpara, Tatjana
Abstract: Catheter ablation (CA) of atrial fibrillation (AF) is the therapy of choice for the maintenance of sinus rhythm in patients with symptomatic AF. Time towards interventional treatment and peri-procedural management of patients undergoing AF ablation may vary in daily practice. The scope of this European Heart Rhythm Association (EHRA) survey was to report the current clinical practice regarding the management of patients undergoing AF ablation and physician's adherence to the European Society of Cardiology Guidelines and the EHRA/HRS/ECAS expert consensus statement on the CA for AF. This physician-based survey was conducted among EHRA members, using an internet-based questionnaire developed by the EHRA Scientific Initiatives Committee. A total of 258 physicians participated in the survey. In patients with paroxysmal or persistent AF, 42 and 9% of the physicians would routinely perform AF ablation as first-line therapy respectively, whereas 71% of physicians would consider ablation as first-line therapy in patients with symptomatic AF and left ventricular ejection fraction <35%. Only 14% of the respondents manage cardiovascular risk factors in patients referred for CA using a dedicated AF risk factor management programme. Radiofrequency CA is the preferred technology for first-time AF (56%), followed by cryo-balloon CA (40%). This EHRA survey demonstrated a considerable variation in the management of patients undergoing AF ablation in routine practice and deviations between guideline recommendations and clinical practice.